2023
DOI: 10.1093/rap/rkae001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Italian version of the ANCA-associated vasculitis patient-reported outcome (AAV-PRO) questionnaire

Elena Treppo,
Miriam Isola,
Maria De Martino
et al.

Abstract: Objectives The primary objective of this study is the translation and validation of the ANCA-associated vasculitis patient-reported outcome (AAV-PRO) questionnaire into Italian, denoted as AAV-PRO_ita. The secondary objective is to evaluate the impact of AAV on Quality of Life(QoL) and work impairment in a large cohort of Italian patients. Methods The study design employs a prospective cohort study approach. First, the AAV-PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated the influence of factors such as sex, GC therapy, and disease history (e.g. disease duration, previous relapses) on patients' perception of their disease (118)(119)(120). Furthermore, since AAV is a multisystemic disorder, managing comorbidities, both pre-existing and subsequent to the diagnosis of AAV, is crucial (121).…”
Section: Unmet Needs In Aavmentioning
confidence: 99%
“…Studies have demonstrated the influence of factors such as sex, GC therapy, and disease history (e.g. disease duration, previous relapses) on patients' perception of their disease (118)(119)(120). Furthermore, since AAV is a multisystemic disorder, managing comorbidities, both pre-existing and subsequent to the diagnosis of AAV, is crucial (121).…”
Section: Unmet Needs In Aavmentioning
confidence: 99%